A new redefinition of geodetic and plane coordinates on UTM geodetic markers / Jeng U Liew ... [et al.] - Jeng, U Liew; Md Din, Ami Hassan; M Idris, Khairulnizam; Hamden, Mohammad Hanif; Zulkifli, Nur Adilla; Ansar, Andy Mohd Hairy (Universiti Teknologi MARA, Shah Alam: Faculty of Architecture, Planning and Surveying, 2020)
The entire Peninsular Malaysia is situated on Sunda Tectonic Plate, which is subjected to motion at a prominent rate. All the geodetic infrastructures, including geodetic markers, benchmarks, Continuous Operating Reference Stations and Cadastral Reference Marks have moved away from their original position, and their existing coordinates are no longer reliable and secure to use. There are 10 geodetic markers around UTM that are subjected to the issue above. This study aims to redefine new geodetic and plane coordinates on UTM geodetic markers. Two units of Trimble NetR9 Geodetic Type Receiver are used to execute 3D GNSS Control Network on geodetic markers as well as Standard Benchmarks. Receiver Independent Exchange data of Continuous Operating Reference Stations and gravimetric geoid of MyGeoid model are retrieved from Department of Survey and Mapping Malaysia. Trimble Business Center, Golden Surfer 8 and StarNet are used as post-processing, geoid interpolation and one-dimensional network adjustment software, respectively. New sets of geodetic and plane coordinates along with orthometric heights are produced for these 10 geodetic markers. Eventually, UTM geodetic markers are tied to Geocentric Datum Malaysia 2000 (2016) and National Geodetic Vertical Datum, providing reliable horizontal and vertical reference for land surveying work to fulfil both industrial and educational purposes.